ADOPSI TEKNOLOGI PENGGUNAAN VARIETAS UNGGUL BARU PADA USAHATANI PADI SAWAH DI DESA PENDEM KOTA BATU - Lestari, Ria; Nurhananto, Dwi Asnawi; Masduki, Said (Universitas Tribhuwana Tunggadewi, 2019)
Seed is an important factor that determines the yield of rice plants. Seeds along with other means of production such as fertilizer, water, light, climate determine the level of crop yield. Although there are sufficient other means of production available, but if low quality seeds are used, the yield will be low. High-quality seeds are obtained from superior seed varieties. The number of new superior varieties produced is not optimally applied by farmers, while the attitude of farmers is a major factor in technology adoption. Therefore, the increase in rice production must be achieved by the use of new superior varieties with integrated plant and resource management (PTT) approaches that are site-specific, adapted to the technology assemblies arranged according to the East Java Agricultural Technology Assessment Center (BPTP). This study aims to determine the adoption of technology to use new high yielding varieties in lowland rice farming. The adoption of technology for the use of new superior varieties in lowland rice farming in Pendem Village, Junrejo District, Batu City is at a low level with a percentage of 31.43%. The method of analysis in this study uses a Likert scale by analyzing questionnaire and interview data containing the method of conducting farming. The question points are adjusted to the technological assemblies of using new high yielding varieties. Benih merupakan faktor penting yang menentukan hasil tanaman padi. Benih bersama dengan sarana produksi lainnya seperti pupuk, air, cahaya, iklim menentukan tingkat hasil tanaman. Walaupun tersedia sarana produksi lain yang cukup, tetapi bila digunakan benih bermutu rendah maka hasilnya akan rendah. Benih bermutu tinggi diperoleh dari varietas benih yang unggul. Banyaknya varietas unggul baru yang dihasilkan tidak diaplikasikan secara optimal oleh petani, sedangkan sikap petani merupakan faktor utama dalam adopsi teknologi. Oleh karena itu peningkatan produksi padi harus dicapai dengan penggunaan varietas unggul baru dengan pendekatan pengelolaan tanaman dan sumber daya terpadu (PTT) yang bersifat spesifik lokasi yang disesuaikan dengan rakitan teknologi yang disusun menurut Balai Pengkajian Teknologi Pertanian (BPTP) Jawa Timur. Penelitian ini bertujuan untuk mengetahui adopsi teknologi penggunaan varietas unggul baru pada usahatani padi sawah. Adopsi teknologi penggunaan varietas unggul baru pada usahatani padi sawah di Desa Pendem Kecamatan Junrejo, Kota Batu berada pada level rendah dengan persentase 31,43%. Metode analisis pada penelitian ini menggunakan skala Likert dengan menganalisis data kuesioner dan wawancara yang berisikan tentang metode pelaksanaan usahatani. Poin-poin pertanyaan disesuaikan dengan rakitan teknologi penggunaan varietas unggul baru.